2016
DOI: 10.1590/0103-8478cr20160081
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of eggs and oocysts of gastrointestinal parasites in passerine birds kept in captivity in Para State, Brazil

Abstract: The objective of this study was to detect helminth eggs and protozoan oocysts in samples of feces from birds of the order

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…The higher prevalence of Isospora spp. in wild, domiciled birds in this study aligns with the findings reported byMagalhães-Matos et al (2016) among captive birds in Pará.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The higher prevalence of Isospora spp. in wild, domiciled birds in this study aligns with the findings reported byMagalhães-Matos et al (2016) among captive birds in Pará.…”
supporting
confidence: 92%
“…Therefore, the low level of positivity among the birds raised in a collective environment may also be due to the fact that most of these birds were acquired legally, which would indicate greater responsibility on the part of the guardian, not only in terms of legal acquisition but also in terms of knowing how to handle these animals correctly. In collective enclosures, stress related to capture and inadequate hygiene are known to favor parasitic, fungal and bacterial infections (Joseph, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations